1999
DOI: 10.1034/j.1600-0420.1999.770516.x
|View full text |Cite
|
Sign up to set email alerts
|

Vernal keratoconjunctivitis in a Stockholm ophthalmic centre ‐ epidemiological, functional, and immunologic investigations

Abstract: ABSTRACT.Purpose: To classify a cohort of 62 patients with vernal keratoconjunctivitis (VKC) in immunologic, functional, and epidemiological terms. Methods: A retrospective chart review was conducted to establish the patients' ethnic origin and to ascertain the results of standard in vitro and in vivo testing for atopic allergy. The latter data were compared with tear Phadiatop A , an allergy screening test, in 31 subjects. Further subgroup analyses included methacholine bronchial provocations, serum screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 22 publications
3
31
0
2
Order By: Relevance
“…3a). The total area (11,259.76 ± 4,498.66 μm 2 ) and percentage area (7.10 ± 2.73%) decreased (to 695.16 ± 469.60 μm 2 and 0.45 ± 0.30%) at the last observation (Fig. 3b, d (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a). The total area (11,259.76 ± 4,498.66 μm 2 ) and percentage area (7.10 ± 2.73%) decreased (to 695.16 ± 469.60 μm 2 and 0.45 ± 0.30%) at the last observation (Fig. 3b, d (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Montan et al [2] found that conjunctival biopsy specimens taken from patients with VKC showed higher counts for dendritic cell markers, including HLA-DR (MHC class II), FcεRI, and CD1a, than in healthy control subjects. Large numbers of dendritic cells distributed in the bulbar conjunctiva, limbus, and peripheral cornea of VKC have also been discovered on in vivo confocal microscopy [23].…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of vernal conjunctivitis in our study could be due to the fact that the work was carried out in the rainy season when pollen is normally dispersed into the atmosphere. In Stockholm, Sweden, using a cohort of 62 patients with vernal keratoconjunctivitis (VKC), VKC was observed to be more common among individuals of Asian and African origin, with varying prevalence among the different ethnic groups suggested as being due to genetic factors [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies provide accurate calculations of VKC prevalence in the general population in European Union (EU), Asia, America or Africa, epidemic characteristics have been described in case series [2][3][4]. In one epidemiological report from Sweden, prevalence of VKC was clearly augmented by immigration of children with an African and Asian origin [16], suggesting that both genetic and environmental factors are implicated in the incidence of the disease.…”
Section: Vernal Keratoconjunctivitismentioning
confidence: 99%